Energy management strategy of multi-stack hydrogen fuel cell system considering aging factors - Ait El Mahjoub Jihane; Olivier Jean-Christophe; Machmoum Mohamed; Laghrouche Salah (EPJ Web of Conferences)
As the demand of low-emission systems grows, hydrogen fuel cells have emerged as a viable and innovative option for sustainable energy applications. This paper explores the implementation of a multi-stack hydrogen Fuel cell system in the context of maritime transportation. The study focuses on addressing two critical challenges: the significant power need of the heavy transport and the aging factor of the stacks. To tackle these issues, an optimized energy management strategy is suggested. This strategy ensures a balanced distribution of the losses across the stacks based on their state of health. In addition to the energy management strategy’s aspects mentioned, a comparison is carried out. The studied strategy is evaluated against others based on a current and a cost analysis. This comparison includes a classical option and the strategy that focuses on minimizing hydrogen consumption. This comparison shows the contribution of the studied strategy in improving other performance criteria as well.